GAMBARAN PENGETAHUAN MAHASISWA BARU PENJASKESREK UNMUS TERHADAP PENYAKIT MALARIA DI PAPUA SELATAN - Febry Ramadhani Suradji; Ronald, Pricilya Margaretha Warwuru, Ade Yuni Sahruni (CV. Adiba Aisha Amira, 2024)
Malaria is still one of the main health problems in the South Papua region. This research aims to determine the knowledge of new Penjaskesrek students regarding malaria in South Papua. This research is descriptive research conducted through interviews and filling out questionnaires with students as respondents. The population of this study were all new Penjaskesrek students in semester 1 and samples were taken using the cluster random sampling method. The results showed that the majority of respondents had suffered from malaria (60.4%). Regarding respondents' knowledge regarding the causes of malaria, most of them answered by mosquitoes (80.2%), but only 42.7% correctly answered by the bite of the Anopheles mosquito. Students' knowledge about the symptoms of malaria, namely high fever, chills and sweating (67%), mosquito breeding places in standing water is 13.5%, how to prevent mosquito bites by using mosquito nets (80.2%), curing malaria by taking medicine and maintaining it. personal and environmental health (75%) and the time when mosquitoes bite is night and day (37.5%).